The Rise of the Guest Editor—Discontinuities of Editorship in Scholarly Publishing - Knöchelmann, Marcel; Hesselmann, Felicitas; Reinhart, Martin; Schendzielorz, Cornelia (Frontiers in Research Metrics and Analytics, 2022)
Scholarly publishing lives on traditioned terminology that gives meaning to subjects such as authors, inhouse editors and external guest editors, artefacts such as articles, journals, special issues, and collected editions, or practices of acquisition, selection, and review. These subjects, artefacts, and practices ground the constitution of scholarly discourse. And yet, the meaning ascribed to each of these terms shifts, blurs, or is disguised as publishing culture shifts, which becomes manifest in new digital publishing technology, new forms of publishing management, and new forms of scholarly knowledge production. As a result, we may come to over- or underestimate changes in scholarly communication based on traditioned but shifting terminology. In this article, we discuss instances of scholarly publishing whose meaning shifted. We showcase the cultural shift that becomes manifest in the new, prolific guest editor. Though the term suggests an established subject, this editorial role crystallizes a new cultural setting of loosened discourse communities and temporal structures, a blurring of publishing genres and, ultimately, the foundations of academic knowledge production.